TWO CENTURIES OF CZECH EXPLORATION OF RUSSIA: TRAVEL BOOKS IN THE CZECH NATIONAL REVIVAL PERIOD - Tomášek, Martin (Porównania, 2019)
The study explores the ambiguities of Czech relations with contemporary Russia seeking their historical roots in the pictures of the Russian reality constructed in Czech period travel books. The travelogue production was characterized by a relatively low number of publications and remarkable heterogeneity. Between the end of the 18th century and the beginning of the 1940s this genre included not only authentic travelogues – travel reportage and business travelogue – but also fictitious travelogues or travelogue imitations, scientific travel books as well as compilations of texts on related topics compensating for restrained opportunities to travel. This repertoire provided Czech readers with rather limited possibilities for getting to know contemporary Russia through the personal experiences of their fellow countrymen, nevertheless, it shows the readers’ interest in the Slavonic East. These period pictures do not tend to evaluate Russia in a specific or prescribed way.